Koordinasi Kelembagaan dalam Penenggelaman Kapal Hasil Tindak Pidana Di Bidang Perikanan - Adam, Sherly (Faculty of Law, Universitas Pattimura, 2020)
His study aims to determine to examine, analyze coordination between institutions in the framework of sinking vessels resulting from criminal acts in the field of fisheries. This research is a normative legal research (legal research). The research began with an inventory of legal regulations or laws and regulations relating to coordination between institutions in the framework of sinking vessels resulting from criminal acts in the field of fisheries. According to the Law, there are two methods of sinking ships carried out by the Government of the Republic of Indonesia, namely sinking ships through a court decision and being caught red-handed. For this reason, there is coordination between institutions in the framework of sinking fishing vessels by the Minister of Maritime Affairs and Fisheries (government) of the Republic of Indonesia, but the coordination of these institutions has not yet been implemented or carried out properly. This is due to unclear regulations regarding operational standards or guidelines for the destruction or sinking of fishing vessels which regulate the implementation, mechanism, and procedure for the destruction of ships to be used as a basis for the Ministry of Maritime Affairs and Fisheries, Prosecutors' Office and the Courts in sinking fishing vessels conducting Illegal Fishing in Indonesian waters.